Introduction to the Special Section of Papers from the 6th GLOBALEX Workshop on Lexicography and Neology - Klosa-Kückelhaus, Annette; Kernerman, Ilan (Lexikos, 2025)
Introduction to the Special Section of Papers from the 6th GLOBALEX Workshop on Lexicography and Neology